Rezension von: Journal of salt history Vol. 1 - Weber, Raimund J. (Württembergisch Franken, 1994)
Journal of Salt-History. Annales d’Histoire du Sei. Jahrbuch für Salzgeschichte. Review of the International Commission for the History of Salt (CIHS), Volume 1 (hrsg. von Jean-Claude Hocquet, Carl D. Litchfield, Rudolf Palme und Peter Piasecki), Schwaz (Berenkamp) 1993. 176 S.